Response of Rabi Cereals to Levels and Methods of Nitrogen Application under Dryland Conditions of Eastern U.P. - Singh, U N; Singh, R A (Annals of Arid Zone, 2016)
Field experiments were conducted in rabi seasons of 1971-72 and 1972-13 to study the effects of the levels and methods of nitrogen application in rabi cereals under dryland condition. Barley was found to be the most suitable rabi cereal as compared to wheat and oat under dryland conditions of eastern U. P. There was a significant response upto 90 kg. N/ha There was better utilization of nitrogen at lower rates as compared to higher rates. A significant response due to split application of nitrogen as soil placementÂ· (basal) (60 kg N/ha) + foliar spray (30 kg. N/ba) was obtained. Top dressing in addition to soil placement (basal) was least effective. Split application of N as foliar in addition to soil placement was more economical.